In-Situ Nanoparticles: A New Strengthening Method for Metallic Structural Material - Shiwei Pan; Xianglin Zhou; Kaixuan Chen; Ming Yang; Yudong Cao; Xiaohua Chen; Zidong Wang (Applied Sciences, 2018)
Over the past several years, coherent interface strengthening was proposed and has since drawn much attention. Unfortunately, many fabrication techniques are restricted to very small size. Recently, a brand new method of in-situ nanoparticle strengthening was systematically investigated, which was proved to be an efficacious way to optimize microstructure and improve mechanical property by utilizing uniformly dispersed nanoparticles. In this review, we summarized recent related advances in investigated steels and Cu alloys, including details of preparation technique and characterization of in-situ nanoparticles. In-situ nanoparticles formed in the melt possess a coherent/semi-coherent relationship with the matrix, which has a similar effect of coherent interface strengthening. In this case, bulk metallic structural materials with dispersed nanoparticles in the matrix can be fabricated through conventional casting process. The effects of in-situ nanoparticles on grain refinement, inhibiting segregation, optimizing inclusions and strengthening are also deeply discussed, which is beneficial for obtaining comprehensive mechanical response. Consequently, it is expected that in-situ nanoparticle strengthening method will become a potential future direction in industrial mass production.